VIEWS ON ETHNOPONYMS OF ARABICS LIVING IN CENTRAL ASIA - Iskanderov Sherzod Abdiganievich (Scholar Express Journal, 2023)
In this article analyzed views on ethnoponyms of Arabian living in Central Asia. In addition author tried to illustrate scientific views of Uzbekistan. As a result of this analyze author give several suggestions and recommendations for social science.
Keywords: ethnoponyms; Arabic; Central Asia; nomadic culture